Radioactive: Real College Podcast - Radio K (KUOM). University of Minnesota (My University, 2017)
This week we play with this years Radio K's pledge week theme: Radioactive. Some stories about Radio K, radio in general, and radioactivity as well.
Runtime (31:24).